Expression of functional recombinant human growth hormone in transgenic soybean seeds - Cunha, Nicolau B.; Murad, André M.; Cipriano, Thaís M.; Araújo, Ana Cláudia G.; Aragão, Francisco J. L.; Leite, Adilson; Vianna, Giovanni R.; McPhee, Timothy R.; Souza, Gustavo H. M. F.; Waters, Michael J.; Rech, Elíbio L. (Transgenic research, 2011)
We produced human growth hormone (hGH), a protein that stimulates growth and cell reproduction, in genetically engineered soybean [ Glycine max (L.) Merrill] seeds. Utilising the alpha prime (α′) subunit of β-conglycinin tissue-specific promoter from soybean and the α-Coixin signal peptide from Coix lacryma - jobi , we obtained transgenic soybean lines that expressed the mature form of hGH in their seeds. Expression levels of bioactive hGH up to 2.9% of the total soluble seed protein content (corresponding to approximately 9 g kg −1 ) were measured in mature dry soybean seeds. The results of ultrastructural immunocytochemistry assays indicated that the recombinant hGH in seed cotyledonary cells was efficiently directed to protein storage vacuoles. Specific bioassays demonstrated that the hGH expressed in the soybean seeds was fully active. The recombinant hGH protein sequence was confirmed by mass spectrometry characterisation. These results demonstrate that the utilisation of tissue-specific regulatory sequences is an attractive and viable option for achieving high-yield production of recombinant proteins in stable transgenic soybean seeds.